Transformasi Karier Melalui Perancangan Sistem Informasi Bursa Kerja Pada SMKN 2 Padang Panjang - Efmi, Efmi Maiyana; Giatman; Nurhasan Syah; Supratman Zakir (AI Society & STMIK Indonesia, 2024)
Career transformation is becoming increasingly important in this digital era, especially in educational institutions such as Vocational High Schools (SMK). There are still many graduates who have not obtained employment opportunities at SMKN 2 Padang Panjang, which is the main reason for the school to establish a Job Exchange information system. An efficient and integrated labour market information system can help alumni find various career opportunities, understand what the labour market needs, and make better career plans. This study looks at ways to improve the availability of job information, increase alumni engagement in job search, and strengthen links between SMK and industry. This study provides practical guidance for SMKs to adopt and implement an effective job fair information system, using the Research and Development (Rnd) method, so that they can make a real contribution in mentoring alumni. This guidance is provided using an appropriate system design approach.